

Studio MT
Giới thiệu về bản thân



































a) x²+5x−3m=0
Để phương trình có 2 nghiệm $x_{1}$, $x_{2}$ ta có :
⇔ Δ ≥ 0 ⇒ 12m+25 ≥ 0
⇒12m≥−25 ⇒m≥$\frac{-25}{12}$
b) Theo Viète ta có: $\left \{ {{x_{1}+x_{2}=-5} \atop {x_{1}x_{2}=-3m}} \right. $
Ta có: $\frac{2}{x_{1}^2}$ + $\frac{2}{x_{2}^2}$ = $\frac{2x_{1}^2 + 2x_{2}^2}{x_{1}^{2}x_{2}^{2}}$ = $\frac{2(x_{1}^{2}+x_{2}^{2})}{(x_{1}x_{1})^{2}}$ = $\frac{50+12m}{9m^2}$
$\frac{2}{x_{1}^2}$ · $\frac{2}{x_{2}^2}$ = $\frac{4}{(x_{1}x_{1})^{2}}$ =$\frac{4}{9m^2}$
Vậy $\frac{2}{x_{1}^2}$ và $\frac{2}{x_{2}^2}$ là 2 $n_{0}$ của phương trình:
${x^2}$ - $\frac{50+12m}{9m^2}$ $x$ + $\frac{4}{9m^2}$ = 0
a) x²+5x−3m=0 ⇒Δ=b²−4ac=52−4·(−3m)=12m+25
Để phương trình có 2 nghiệm $x_{1}$, $x_{2}$ ta có :
⇔Δ≥0⇒12m+25≥0
⇒12m≥−25
⇒m≥$\frac{-25}{12}$
b) Theo Viète ta có:
$\left \{ {{x_{1}+x_{2}=-5} \atop {x_{1}x_{2}=-3m}} \right. $
Ta có: $\frac{2}{x_{1}}$ + $\frac{2}{x_{2}}$ = $\frac{2x_{1} + 2x_{2}}{x_{1}^{2}x_{2}^{2}}$ = $\frac{2(x_{1}^{2}+x_{2}^{2})}{(x_{1}x_{1})^{2}}$ = $\frac{50+12m}{9m^2}$
$\frac{2}{x_{1}}$ · $\frac{2}{x_{2}}$ = $\frac{4}{(x_{1}x_{1})^{2}}$ =$\frac{4}{9m^2}$
Vậy $\frac{2}{x_{1}}$ và $\frac{2}{x_{2}}$ là 2 $n_{0}$ của phương trình:
${x^2}$ - $\frac{50+12m}{9m^2}$ $x$ + $\frac{4}{9m^2}$ = 0